Discharge pulses of hydroelectric dams and their effects in the downstream limnological conditions: A case study in a large tropical river (SE Brazil) - De Oliveira Naliato, Danilo A. [UNESP]; Nogueira, Marcos Gomes [UNESP]; Perbiche-Neves, Gilmar [UNESP] (Wiley, 2009)
To address daily fluctuations in electricity demands, the quantities of water passing through the turbines of hydropower plants can vary significantly (up to fourfold) during a 24-h cycle. This study evaluates the effects of hourly variations in water discharges on the limnological conditions observed in two below-dam river stretches. The study reservoirs, Capivara and Taquaruçu, are the 9th and 10th reservoirs in a cascade of dams in the Paranapanema River in south-east Brazil. The reservoirs exhibit different trophic conditions, water retention times, thermal regimes and spillway positions. Capivara Reservoir is deeper, meso-eutrophic, with a high water retention time and hypolimnetic discharges (32 m) varying between 500 and 1400 m3 s-1. In contrast, Taquaruçu Reservoir is relatively shallow, oligo-mesotrophic, and has a low retention time, with water discharges varying between 500 and 2000 m3 s-1. Its turbine water intake zone also is more superficial (7 m). For two periods of the year, winter and summer, profiles of limnological measurements were developed in the lacustrine (above-dam site) zones of the reservoirs, as well as in the downstream river stretches (below-dam site). In both cases, the sampling was carried out at 4-h intervals over a complete nictemeral cycle. The results demonstrated that the reservoir operating regime (water discharge variations) promoted significant differences in the conditions of the river below the dams, especially for water velocity, turbidity, and nutrient and suspended solids concentrations. The reservoir physical characteristics, including depth, thermal stratification and outlet structure, are also key factors influencing the limnology and water quality at the below-dam sampling sites. In the case of Capivara Reservoir, for example, the low dissolved oxygen concentration (<5.0 mg L-1) in its bottom water layer was transferred to the downstream river stretches during the summer. These study results demonstrated that it is important to continue such investigations as a means of verifying whether or not these high-amplitude/low-frequency variations could negatively affect the downstream river biota. © 2009 The Authors. Journal compilation © 2009 Blackwell Publishing Asia Pty Ltd.
Keywords: Cascade reservoirs; Dam operation; Hourly variation; Limnological variables; concentration (composition); dam; discharge; dissolved oxygen; hydroelectric power plant; limnology; reservoir; retention; spillway; surface water; thermal regime; water quality; Brazil; Paranapanema River; South America